Specialized Register and Intertextuality in Twitter's Movie Enthusiast Community: A Discourse Analysis - Ferdiana, Andini; Indah, Rohmani Nur (ITScience (Information Technology and Science), 2025)
This research explores the intertextuality found in the specialized registers used by movie enthusiast communities on Twitter. With the rapid growth of digital communication and community-based discourse on platforms like Twitter, this study investigates how specific language and references, such as tweets and movie-related terminology are shaped by intertextuality and paratext elements. The research aims to identify types of intertextuality within these registers and analyze how they are formed and function in fostering shared meaning among community members. Using a qualitative exploratory approach, this study employs discourse analysis with intertextuality theory by Julia Kristeva (1980) and paratext theory by Jonathan Gray (2010) as its theoretical foundation. The data consists of 21 tweets and posts collected from the “Movie Twitter” community, which were selected based on their relevance to cinematic discourse and use of English-language specialized registers. The analysis reveals that most registers exhibit conventional and indirect intertextuality, supported by paratext elements such as trailers, reviews, and fan theories that guide or shape audience interpretation. These linguistic practices help reinforce cultural continuity within the community, enabling users to participate in a collective interpretive space. The findings suggest that intertextual registers not only enhance discourse cohesion but also contribute to audience engagement and meaning-making processes. The study recommends further research on intertextuality in other online subcultures and highlights the importance of digital literacy in understanding cultural communication.